2018
DOI: 10.1016/j.jare.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Solid electrolytes based on {1 − (x + y)}ZrO 2 -(x)MgO-(y)CaO ternary system: Preparation, characterization, ionic conductivity, and dielectric properties

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The transmittance enhancement of the broad peak at 1411 cm -1 may be caused by the C=C stretching vibration in the benzene ring of MG. The Mg-O-Mg vibration modes of MgO [37] appeared between 750 cm -1 and 583 cm -1 . The peak at 1624 cm -1 and 3420 cm -1 was due to H-O-H bending vibration and stretching vibration of -OH of adsorbed water, respectively [9, 38].…”
Section: Resultsmentioning
confidence: 99%
“…The transmittance enhancement of the broad peak at 1411 cm -1 may be caused by the C=C stretching vibration in the benzene ring of MG. The Mg-O-Mg vibration modes of MgO [37] appeared between 750 cm -1 and 583 cm -1 . The peak at 1624 cm -1 and 3420 cm -1 was due to H-O-H bending vibration and stretching vibration of -OH of adsorbed water, respectively [9, 38].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that double cation doped ZrO 2 could reduce the test temperature and improve its conductivity when compared to the single cation stabilized zirconia [25,26,27,28,29,30]. For instance, Liu et al found that 1 wt % Al 2 O 3 doped 8 mol % Y 2 O 3 stabilized ZrO 2 (8YSZ) reduced the sintering temperature of YSZ and improved the output of the fuel cell [26].…”
Section: Introductionmentioning
confidence: 99%